DEVELOPMENT OF ANDROID-BASED DIGITAL POCKET LEARNING MEDIA TO INCREASE STUDENT'S INTEREST AND LEARNING OUTCOMES IN IPS LEARNING - Maria Dewi Ratna Simanjuntak; Dede Ruslan; Naeklan Simbolon (Sensei International Journal of Education and Linguistic, 2021)
This study aims to describe the level of feasibility and effectiveness of developing android-based digital pocketbook learning media to increase student interest and learning outcomes in social studies learning for class IV. This research was conducted at the Pembina Experimental Elementary School, Medan, North Sumatra. The subjects of this study were all fourth-grade students of the Medan Pembina Experiment Elementary School for the 2020/2021 academic year, totaling 60 students. This research method is ADDIE development research. The results showed (1) Based on the validity of material experts 92.5%%, design experts 80%, and linguists 90%. From the results of the validation of the developed media, the media is included in the perfect criteria and is declared valid and feasible to use; (2) Learning Media for Android-Based Digital Pocket Books is categorized as practical because the media resulting from student responses from the first and second trials has increased; and (3) Based on the research results, the Android-based digital pocketbook learning media is said to be effective in learning with the assumption that students' social studies learning value is higher when using Android-based digital pocketbook learning media.